GENERAL ASPECTS OF THE INFLUENCE ON ABIOTIC AND BIOTIC FACTORS OF AQUATIC ECOSYSTEMS OF THE MODERN TECHNOLOGIES ELEMENTS USE - Honcharova, Olena; Korzhov, Yevhen (SWorld-Ger Conference proceedings, 2023)
The article considered the main positive and negative aspects of the modern technological processes use impact on the biotic and abiotic components of aquatic ecosystems. It has been established those modern technologies in aquaculture and fish farming ar